Establishment of a tissue-mimicking surrogate for pulmonary lesions to improve the development of RFA instruments and algorithms - Bühler, Louisa; Enderle, Markus D.; Kahn, Nicolas; Polke, Markus; Schneider, Marc; Heußel, Claus Peter; Herth, Felix; Linzenbold, Walter (Biomedicines, 2022)
(1) Development of radiofrequency ablation (RFA) systems for pulmonary lesions is restricted by availability of human tumor specimens and limited comparability of animal tissue. We aimed to develop a new surrogate tissue overcoming these drawbacks. (2) Reference values for electrical impedance in lung tumor tissue were collected during routine lung tumor RFA (n = 10). Subsequently, a tissue-mimicking surrogate with comparable electrical impedance and facilitating detection of the ablation margins was developed. (3) The mean electrical impedance for all patients was 103.5 ± 14.7 Ω. In the optimized surrogate tissue model consisting of 68% agar solution, 23% egg yolk, 9% thermochromic ink, and variable amounts of sodium chloride, the mean electrical impedance was adjustable from 74.3 ± 0.4 Ω to 183.2 ± 5.6 Ω and was a function (y = 368.4x + 175.2; R2 = 0.96; p < 0.001) of sodium chloride concentration (between 0 and 0.3%). The surrogate tissue achieved sufficient dimensional stability, and sample cuts revealed clear margins of color change for temperatures higher 60 °C. (4) The tissue-mimicking surrogate can be adapted to lung tumor with respect to its electrical properties. As the surrogate tissue allows for simple and cost-effective manufacturing, it is suitable for extensive laboratory testing of RFA systems for pulmonary ablation.